2023
DOI: 10.1371/journal.pone.0286118
|View full text |Cite
|
Sign up to set email alerts
|

The role of perceived social norms in non-suicidal self-injury and suicidality: A systematic scoping review

Abstract: Social norms are an important influence on health-related behaviours and intention formation. As both suicidal behaviour and non-suicidal self-injury (NSSI) can be motivated by intentions, perceived social norms may have an important role in suicide and NSSI outcomes, although no existing reviews of this association exist. Following the PRISMA Scoping Review extension guidance, a scoping review based on systematic searches of key databases was conducted to identify published English language studies investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 129 publications
0
1
0
Order By: Relevance
“…The proportion of articles in our sample attributing legal and social or relationship problems as circumstances to each gender is opposite of the proportions of disclosed circumstances in the National Violent Death Reporting System [ 6 ]. Increased stigmatizing language in reports of women experiencing legal problems and men experiencing relationship problems may be attributed to their perceived deviation from social norms [ 39 ]. Reports of female deaths not attributed to any circumstance were more linguistically similar to the stigma attitude than reports of male deaths—demonstrating the presence of discernable stigmatizing language even without specifying the circumstances of suicide.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of articles in our sample attributing legal and social or relationship problems as circumstances to each gender is opposite of the proportions of disclosed circumstances in the National Violent Death Reporting System [ 6 ]. Increased stigmatizing language in reports of women experiencing legal problems and men experiencing relationship problems may be attributed to their perceived deviation from social norms [ 39 ]. Reports of female deaths not attributed to any circumstance were more linguistically similar to the stigma attitude than reports of male deaths—demonstrating the presence of discernable stigmatizing language even without specifying the circumstances of suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings from a sample of people who all had a history of self-harm would be consistent with this. There has been little research investigating the influence of perceived social norms of NSSH (including anticipation of social approval/ sanctions and misperceptions of others' NSSH rates) on own NSSH (Dempsey et al, 2023), and more work is needed to understand how these modify the effects of direct exposure to peer NSSH. Our findings regarding the wash-out are consistent with evidence that adolescents demonstrate sensitivity to the quality of social information, integrating safe social information into their decision-making (Ciranka & Van Den Bos, 2019).…”
Section: Individuals Registeredmentioning
confidence: 99%
“…However, compared to suicidal ideation, NSSI leaves physical traces on the body, such as cuts and cigarette burns, which implies that NSSI is easier to be discerned than is suicidal ideation (12). Previous studies have demonstrated that NSSI can significantly predict suicidal ideation (96)(97)(98). Therefore, to improve the precision of discerning suicidal intent, clinical practitioners can pay specific attention to NSSI in adolescents.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%